A7.05 Baricitinib abrogates IFNγ-induced focal adhesion kinase (FAK) activation in fibroblast-like synoviocytes. (24th February 2016) - Karonitsch, T; Wunrau, C; Beckmann, D; Dalwigk, K; Byrne, R; Niederreiter, B; Wanivenhaus, A; Holinka, J; Scheinecker, C; Steiner, G; Smolen, JS; Pap, T; et al.
Abstract : While evidence implicates both the adaptive and innate immune system in rheumatoid arthritis (RA) pathogenesis, accumulating data indicate that the synovial tissue itself actively participates in the destructive inflammatory process. Specifically, resident fibroblast-like synoviocytes (FLS), together with macrophages, re-organise to form an aggressive cell mass, called pannus, which destroys the articular cartilage and the subchondral bone. The exact molecular mechanisms of synovial pannus formation, FLS expansion and invasion into adjacent tissues are not yet known. Our data strongly suggest that the T-cell derived cytokine IFNγ is involved in FLS-mediated joint destruction. Migration and invasion assays revealed increased migratory activity for IFNγ-stimulated FLS, when compared to unstimulated FLS. Further, biochemical studies showed that IFNγ promotes the migratory and invasive activity of FLS via Janus kinase 2 (JAK2) and the focal adhesion kinase (FAK), a kinase known to integrate focal adhesion turnover and thus, regulates cell migration. In detail, IFNγ stimulation of FLS distinctly resulted in the phosphorylation of FAK-Y925, a phospho-site that has recently been demonstrated to be required for FAK-mediated cell migration. siRNA knockdown of JAK2, but not JAK1, abrogated the IFNγ-induced activation of FAK. Correspondingly, baricitinib, a JAK inhibitor that is currently successfully probed in RA clinical trials, abrogated IFNγ-stimulated activation of FAK. In conclusion, our studies contribute insight into the synovial response to IFNγ and reveal JAK2 and FAK as potential targets for synoviocyte-mediated joint destruction in arthritis, especially in RA.